Investigating the mediating role of Self-Differentiation in the relationship between Self-Esteem and Body Image in women - Mahshid Beigi; Roghayeh Mousavi; Vafa Mostafa (مطالعات زن و خانواده, 2022)
Abstract:Purpose: the purpose of this study was to investigate the mediating role of Self-Differentiation between the Self-Esteem and Body image. Methods: this is a descriptive correlational study. The statistical population of the present study includes all Married Women living in Tehran in 2020. That 211 of them were selected by available sampling method and they completed the Body Image Scale, Self-Esteem Scale and Self-Differentiation Questionnaire. the data were analyzed by Pearson Correlation and Path Analysis. Results: the results showed that there is a significant relationship between Body Image, Self-Differentiation and Self-Esteem (p<0.05), and Self-Differentiation in the relationship between Self-Esteem and Body Image, play a mediating role. Conclusion: it can be concluded that Self-Differentiation as a mediator can modify the relationship between Self-Esteem and Body Image. Therefore, the emphasis on Self-Differentiation training can be considered in order to reduce the effects of negative Body Image. The results are discussed. v